Hecate-FSHβ33-53C/S lytic peptide conjugate selectively kills targeted follicle stimulating hormone receptor (FSHR)-positive cancer cells - Rahman, Nafis A.; Chrusciel, Marcin; Ponikwicka-Tyszko, Donata; Pulawska-Moon, Kamila; Stelmaszewska, Joanna; Doroszko, Milena; Kreuzer, Oliver J.; Rivero-Muller, Adolfo; Li, Xiangdong; Ziecik, Adam J.; Wolczynski, Slawomir; Huhtaniemi, Ilpo (Elsevier Masson, 2025)
BACKGROUND
The follicle stimulating hormone (FSH) receptor (FSHR), is expressed primarily in the gonads, also found in ovarian and prostate cancers, and in tumor vessel endothelial cells. We investigated the potential of a targeted cytotoxic approach using Hecate-FSHβ, a conjugate derived from a lytic peptide Hecate, an analog of bee venom melittin, and the β subunit of FSH, to selectively eliminate FSHR-positive cancer cells.
METHODS
Hecate-FSHβ-mediated cytotoxicity was tested in human granulosa tumor cell line KGN, human embryonic kidney HEK-293 cell line stably transfected with human FSHR cDNA (HEK293-FSHR) and mock-transfected HEK-293 cells as FSHR-negative control cells. Tested variant Hecate-FSHβ33-53C/S with cysteine residues replaced by serine, was evaluated for its cytotoxicity towards FSHR-positive cells.
RESULTS
Hecate-FSHβ33-53C/S demonstrated the highest specific cytotoxicity towards FSHR-positive cells (KGN and HEK293-FSHR vs. control). In competition studies, cotreatment with recombinant human FSH (rhFSH) reduced the cytotoxic effect of the conjugate on these cells, highlighting FSHR specificity. In xenograft models of HEK293-FSHR, Hecate-FSHβ33-53C/S alone or in combination with a gonadotropin releasing hormone (GnRH) antagonist (Cetrorelix, CTX) significantly inhibited tumor growth. No synergistic effect was observed with co-administered Hecate-FSHβ33-53C/S and CTX. Hecate-FSHβ33-53C/S induced necrosis in tumor cells, whereas CTX triggered apoptosis. Hecate-FSHβ33-53C/S did not produce any side effects. CTX treatment caused increased spleen size and inhibited spermatogenesis, leading to reduced testis weight, which aligns with expected gonadal effects.
CONCLUSIONS
Hecate-FSHβ33-53C/S is highly effective in selectively targeting and killing FSHR-expressing cancer cells, with minimal side effects, suggesting its potential as a therapeutic option for cancers expressing FSH receptors.